1997
DOI: 10.1128/jvi.71.12.9124-9133.1997
|View full text |Cite
|
Sign up to set email alerts
|

The superantigen-homologous viral immediate-early gene ie14/vsag in herpesvirus saimiri-transformed human T cells

Abstract: Herpesvirus saimiri C488 transforms human T lymphocytes to stable growth in culture. The growth-transformed human T cells harbor the viral genome in a nonintegrated episomal form without production of virus particles. In these cells, virus gene expression was previously found to be confined to the transforming genes stpC and tip. In order to analyze virus gene expression in more detail, we applied a subtractive hybridization technique and compared stimulated virus-transformed cells with uninfected parental T c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
71
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 72 publications
1
71
0
Order By: Relevance
“…We found that the expression of both HVS-flip and HVS-bcl-2 was restricted to cultures with viral replication. Activation with PMA does not induce lytic replication of HVS in human transformed T cells but enhances the expression of some viral genes (17,30). HVS-flip and HVS-bcl-2 transcripts were not detected by Northern blot hybridization in human transformed T cells, neither constitutively nor after activation with PMA ( Fig.…”
Section: Viral Antiapoptotic Genesmentioning
confidence: 93%
See 1 more Smart Citation
“…We found that the expression of both HVS-flip and HVS-bcl-2 was restricted to cultures with viral replication. Activation with PMA does not induce lytic replication of HVS in human transformed T cells but enhances the expression of some viral genes (17,30). HVS-flip and HVS-bcl-2 transcripts were not detected by Northern blot hybridization in human transformed T cells, neither constitutively nor after activation with PMA ( Fig.…”
Section: Viral Antiapoptotic Genesmentioning
confidence: 93%
“…Therefore, we cloned and sequenced the gene coding for HVS-flip of strain C488 that transforms human T cells and found that the amino acid sequence identity of the FLIPs of strains A11 and C488 was 94%. Likewise, the sequence identity of the HVS-Bcl-2 of strains A11 and C488 is 92.5% (30). This suggests that strain-specific sequence differences of the two HVS antiapoptotic genes do not contribute to the different transforming capacities.…”
Section: Viral Antiapoptotic Genesmentioning
confidence: 95%
“…. HVS viral superantigen is expressed in the immediate-early lytic phase and powerfully induces the proliferation of CD4-positive cells (6,14,36). At a position equivalent to that of the HVS viral superantigen, KSHV contains unique membrane proteins called K3, K4.2, and K5 (25).…”
Section: Downregulation Of Surface Expression Of Mhc Class I Moleculementioning
confidence: 99%
“…The expression of viral genes in herpesvirus saimiri-transformed human cells is highly restricted. The bicistronic mRNA carrying the StpC and Tip genes which are essential for viral transformation and the mRNA needed for a putative viral superantigen have been detected in strain C488-transformed human T cells (10,15). In contrast, transcription of various viral genes is detectable from transformed marmoset or rabbit cell lines, where limited viral replication occurs.…”
mentioning
confidence: 99%